2022
DOI: 10.1039/d2ma00171c
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the crystalline phase of binary silicide on its lithiation and delithiation properties

Abstract: The reversible capacity is not dependent on the amount of Si included in the silicide; the capacity was found to be independent on the composition of silicide even in the case of a given transition metal making up the silicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…We reported that pure silicide electrodes exhibited higher lithiation-delithiation plateaus and/or slopes than Si electrodes. [51][52][53] However, the silicide phase in the composite electrode hardly stored Li (although it may have functioned as a Li-diffusion path). 13,54 Table S1 lists Li + diffusion coefficients (D Li+ ) of Si and certain silicides estimated using a galvanostatic intermittent titration technique.…”
Section: Resultsmentioning
confidence: 99%
“…We reported that pure silicide electrodes exhibited higher lithiation-delithiation plateaus and/or slopes than Si electrodes. [51][52][53] However, the silicide phase in the composite electrode hardly stored Li (although it may have functioned as a Li-diffusion path). 13,54 Table S1 lists Li + diffusion coefficients (D Li+ ) of Si and certain silicides estimated using a galvanostatic intermittent titration technique.…”
Section: Resultsmentioning
confidence: 99%
“…We focused on silicides as active anode materials because they exhibit unique metal-like ductility, malleability, and high electron conductivity. 14,15 In particular, A-FeSi 2 has a tetragonal crystal structure and it has been applied in various fields such as solar cells, optical sensors, thermoelectric conversion devices, thermal conductivity materials, and semiconductor devices, owing to its semiconductor properties, optical attributes, and thermal conductivity. 16 The versatility of A-FeSi 2 , which can be tailored to specific applications, is of particular significance in energy-related technologies.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22–23 ] Other Si‐based alloy anodes such as Fe–Si, Cu–Si, and Ni–Si systems also display improved cycling stability. [ 24–28 ] Domi et al. reported that by combining Si with Cu or Fe, the cycling stability could be greatly improved.…”
Section: Introductionmentioning
confidence: 99%